Faking nature : the ethics of environmental restoration - Elliot, Robert, 1950- (Environmental philosophies series., 1997)
Faking Nature is a timely and provocative analysis of the simultaneous destruction and restoration of the natural world and the ethics related to those processes, in an era of accelerated environmental damage and repair.